Ethnobotanical survey of Maytenus ilicifolia Mart. ex Reissek in a rural community in the Southwest of Paraná, Brazil - Moura, Amanda Pacheco Cardoso; Salla, Vanessa Padilha; De Lima, Daniela Macedo; Zulian, Daniele Fernanda [UNESP] (My University, 2018)
Introduction: Maytenus ilicifolia Mart. ex Reissek belongs to the Celastraceae family. Native to Brazil, this plant grows mainly in the south of the country. Use of medicinal plants is very common in Brazil, and studies based on data about their popular use and knowledge are of great interest. The low cost of natural medicine stimulates the use of medicinal plants in the public health network. These are mainly destined for poor populations, which has become common practice in the case of the species M. ilicifolia. Objective: Conduct an ethnobotanical survey about the use of M. ilicifolia and other species with medicinal properties in the rural community of São Cristóvão, municipality of Dois Vizinhos, in the southwest region of the state of Paraná. Methods: Data were obtained from visits to 19 households in the community from May to July 2011. Quantitative analysis was performed and a thirteen-item questionnaire was developed. Results: It was found that in 70.58 % of the households visited M. ilicifolia was grown either in the backyard or in nearby land plots. Medicinal plants are grown by 89.47 % of the households. These include 37 species from 35 genera and 20 families. Conclusions: It was concluded that respondents grow a variety of medicinal species, including M. ilicifolia. This habit was found to be common in the region. However, it was observed that medicinal plants are not used as a source of family income.
Estudio etnobotánico de Maytenus ilicifolia Mart. ex Reissek en una comunidad rural en el Sudoeste de Paraná, Brasil
Levantamento etnobotânico de Maytenus ilicifolia Mart. ex Reissek em uma comunidade rural do Sudoeste do Paraná, Brasil
Keywords: Celastraceae; Ethnobotany; Medicinal plants; Phytotherapeutic properties; Popular use